Environmental Quality Monitoring of Road Preservation in the Paal X Area - Adriansyah, Endi; Nalendra, Brama; Radinal; Qolbi, M. Khofidul; Syahfutra, Juanda Edo; Sufra, Rifqi; Syaiful, M.; Putri, Silvia Devi Eka; Dony, Wari (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
Transportation plays a very important role in economic development in Indonesia. The contribution of construction services to national development is very large, especially in preparing road facilities and infrastructure which have a great influence on economic development in Indonesia. In order to integrate the transportation system in Indonesia, this indicates the increasing number of road maintenance project activities. Jambi Province has a national road where road maintenance activities are carried out every year. The increasing number of road maintenance activities means that based on existing regulations, it is important to carry out environmental testing during the construction period. The purpose of this study is to carry out environmental testing on the Preservation work of the X road section which includes surface water analysis, ambient air testing, n. The method used in this study is descriptive quantitative, the quality standards in this test include Government Regulation No. 22 of 2021. The results of this study at the location obtained all test results with the nationally accredited laboratory KAN are still below the environmental quality standard parameters.